Attitude of Students' Interest in Learning Physics - Deborah Masniari. S; Botir T Turaqulov; Josephat Kigo (Schrödinger: Journal of Physics Education, 2023)
Purpose of the study: This study aims to determine students' attitudes towards physics subjects through indicators of adoption of a scientific attitude, interest in increasing the time to study physics and career interest in physics in high schools.. Methodology: This type of research is survey research with the instrument used is a questionnaire. Data analysis in this study used quantitative research using the SPSS program to carry out descriptive statistical tests. The research subjects were 60 students. Quantitative data analysis techniques using descriptive statistics. Main Findings: The results of the analysis obtained from the indicators of adopting a scientific attitude are in the good category. Indicators of interest in increasing the time to study physics and career interest in physics are in the moderate category. Based on these results, students at SMA Negeri 2 Jambi City have an adequate attitude towards learning physics. The results showed that in the first indicator, students' social implications for Physics were included in the good category. In the second indicator, attitudes towards physics investigations are included in the fairly good category. And on the third indicator, the desire to have a career in Physics is included in the good category. Novelty/Originality of this study: Describe how the attitude of students' interest in learning physics in high school.